Decision Support System for Determining Employee Working Time with Analytical Hierarchy Process Method - Essther Ika Chardina (Institute of Computer Science (IOCS), 2021)
Operational work of a company can not be separated from the placement of employee work time. The placement of employees in accordance with their achievements and abilities at the right working time supports the smooth operation of the company's work. In this final project, a decision support system for determining the working time of employees is made by using the Analytical Hierarchy Process (AHP) method. The Analytical Hierarchy Process method is an approach method used to help solve problems that require values ​​based on existing considerations into an easier and structured process. This method is expected to help operational managers in determining the working time of employees.